A Cadaveric Study: Does Ankle Positioning Impact the Quality of Anatomic Syndesmosis Reduction? - Jeffrey A. Foster MD; Arun Aneja MD, PhD; Mark R. Nazal MD, MPH; Jarod T. Griffin MD; Maaz Muhammad MD; Carlos R. Sierra-Arce MS; Wyatt G.S. Southall BS; Robert K. Wagner MD; Jacob S.W. Borgida BS; Thuan V. Ly MD; Arjun Srinath MD, MPH (Foot & Ankle Orthopaedics)
Category: Trauma; Ankle Introduction/Purpose: To compare the quality of syndesmotic reduction with the ankle in maximal dorsiflexion versus neutral plantarflexion (normal resting position). Methods: Two fellowship-trained orthopaedic surgeons disrupted syndesmoses of 10 cadaveric ankle specimens from 5 donors. All ankles were initially placed in neutral plantarflexion and were subsequently reduced and stabilized with one 0.062-inch K-wire in a quadricortical fashion. Post-reduction computed tomography (CT) scans were then obtained. This process was repeated with the ankles placed in maximal dorsiflexion. Post-reduction CT scans were compared to baseline CT imaging obtained prior to syndesmotic disruption. Mixed-effects linear regression was used to assess differences between baseline scans and reduction in neutral plantarflexion and maximal dorsiflexion with significance set at P< 0.05. Results: Syndesmotic reduction and stabilization in maximal dorsiflexion led to increased external rotation of the fibula compared to baseline scans [13.0 degrees ± 5.4 degrees (mean ± SD) vs. 7.5 degrees ± 2.4 degrees, P=0.002]. There was a tendency towards lateral translation of the fibula with the ankle placed in maximal dorsiflexion (3.3 mm ± 1.0 mm vs. 2.7 mm ± 0.7 mm, P=0.096). No other statistically significant differences between measurements of reduction with the ankle placed in neutral plantarflexion or maximal dorsiflexion and baseline were present (P>0.05). Conclusion: Reducing the syndesmosis with the ankle in maximal dorsiflexion leads to malreduction with external rotation of the fibula. There was no statistically significant difference in reduction quality with the ankle placed in neutral plantarflexion. Future studies should assess the clinical implications of ankle positioning during syndesmotic fixation.